Newborn Screening using Dried Blood Spot for Seven Metabolic DisordersA Retrospective Study from a Tertiary Care Hospital in Southern India - KARTHIKEYAN KADIRVEL; VINOD BABU SUGUMARAN; SUMATHI SRI RAMACHANDRAN; SOUNDARARAJAN PALANISAMY (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Newborn Screening (NBS) is an important public health measure in many developed countries. In developing countries like India, the benefits of NBS have been acknowledged and that screening is slowly gaining attention. Aim: To estimate the proportion for seven conditions screened in a tertiary care hospital in Southern India namely Congenital Hypothyroidism (CH), Congenital Adrenal Hyperplasia (CAH), Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency, Biotinidase Deficiency (BD), Galactosemia, Phenylketonuria (PKU) and Cystic Fibrosis (CF). Materials and Methods: The present descriptive study was conducted at a tertiary care teaching hospital in Southern India during a three year period between January 2018 to December 2020. A retrospective analysis of the results of NBS by dried blood spots was done. There were 3152 live births during this period out of which 1649 babies were screened (52% coverage). Heel prick samples after 48 hour of life and prior to discharge were analysed by quantitative assessment. Neonates having positive screening results were recalled by telephonic call for confirmatory tests. Results: CH, BD and G6PD deficiency were the most common disorders with a proportion of 1:824, 1:1649 and 1:1649, respectively. Galactosemia, CF and PKU were not found in study population. Conclusion: These results need to be corroborated with larger studies from the same geographical area.